Chopped carbon fiber reinforced silicon carbide ceramic material and preparation method thereof
By using chopped carbon fiber reinforced silicon carbide ceramic materials, the preparation process is simplified, the problem of insufficient toughness of SiC ceramic materials is solved, and the comprehensive performance of high toughness, low density, high compression strength and low friction coefficient is achieved.
Patent Information
- Application Number
- CN202411907328.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
AI Technical Summary
The existing SiC ceramic materials have low toughness and are prone to transcrystal fractures under external forces, which limits their performance in long-term applications.
The preparation process is simplified by using chopped carbon fiber reinforced silicon carbide ceramic materials, SiC powder, dopant and chopped carbon fibers are mixed by ball milling, and the pre-sintering and densification sintering are performed after pressing and molding, simplifying the preparation process.
It improves the fracture toughness of the material, has low density, high compression strength, low friction coefficient, and good wear resistance. It is suitable for high-temperature thermal structural materials and extreme environment applications.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite ceramic materials, and in particular to a chopped carbon fiber reinforced silicon carbide ceramic material and a preparation method thereof. Background Art
[0002] Silicon carbide (SiC) ceramics have the advantages of high melting point, high hardness, good chemical stability, wear resistance, and high strength. They are important candidate materials for sealing and can be widely used in mechanical seals, bearings, aerospace and other fields. At the same time, silicon carbide (SiC) materials have the advantages of small neutron absorption cross section, good high-temperature mechanical properties, and high thermal conductivity. They are very promising structural materials in nuclear energy systems. Therefore, SiC ceramic materials can be used in key shaft seal components in the nuclear industry, which is related to the safe operation of the entire nuclear power system. However, the interface bonding between the grains of the SiC ceramic materials usually prepared is strong. Under the action of external force, cracks are easy to expand along the inside of the grains, causing transgranular fracture. Therefore, the toughness of the SiC ceramics currently prepared is low, and the product is brittle, which is not conducive to long-term application.
[0003] Carbon fiber reinforced SiC composite ceramics effectively combine the advantages of silicon carbide ceramic matrix and fiber. While retaining the excellent mechanical and thermal properties of silicon carbide ceramic matrix, it can significantly improve the fracture toughness of the material. These excellent properties make it the first choice for high-temperature thermal structural materials and extreme environment applications. It is widely used in aerospace vehicles, turbine engines, missile nozzles, and lightweight support structure materials. However, the current industrial application of carbon fiber reinforced SiC composite ceramics mainly uses long fibers to prepare silicon carbide composite ceramics. The long fibers need to be woven into felts first, then impregnated with resin or ceramic slurry, cracked after curing, and then impregnated with resin or ceramic slurry. After repeated densification, the desired ceramic products are obtained. The entire process is relatively complicated and has many procedures. Summary of the invention
[0004] The object of the present invention is to provide a chopped carbon fiber reinforced silicon carbide ceramic material and a preparation method thereof. The silicon carbide ceramic material prepared by the present invention simplifies the preparation process while ensuring high toughness.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a chopped carbon fiber reinforced silicon carbide ceramic material, comprising a SiC matrix and a dopant and chopped carbon fibers dispersed in the SiC matrix;
[0007] The dopant includes B, B 4 One or more of C and AlN;
[0008] The chopped carbon fibers have an aspect ratio of greater than 10 and a length of 5 to 30 μm;
[0009] The content of SiC matrix in the chopped carbon fiber reinforced silicon carbide ceramic material is ≥89wt%, the content of dopant is >0 and ≤5wt%, and the content of chopped carbon fiber is >0 and ≤6wt%;
[0010] The toughness of the chopped carbon fiber reinforced silicon carbide ceramic material is 4.0 MPa·m 1 / 2 above.
[0011] Preferably, the compressive strength of the chopped carbon fiber reinforced silicon carbide ceramic material is 2000-3000 MPa.
[0012] Preferably, the density of the chopped carbon fiber reinforced silicon carbide ceramic material is 3.0-3.1 g / cm 3 , the friction coefficient is 0.25~0.3.
[0013] The present invention provides a method for preparing the chopped carbon fiber reinforced silicon carbide ceramic material according to the above scheme, comprising the following steps:
[0014] The SiC powder, dopant powder, water, dispersant, binder and chopped carbon fiber powder are ball-milled and mixed, and then dried and sieved to obtain a mixed powder; the mass of the SiC powder, dopant powder and chopped carbon fiber powder is the same as the mass of the SiC matrix, dopant and chopped carbon fiber in the chopped carbon fiber reinforced silicon carbide ceramic material;
[0015] Pressing the mixed powder into a shape to obtain a green body;
[0016] The green body is subjected to primary sintering and densification sintering in sequence to obtain the chopped carbon fiber reinforced silicon carbide ceramic material.
[0017] Preferably, the dispersant includes one or more of stearic acid, n-butanol, polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate; the amount of the dispersant used is 0.1 to 0.5 wt % of the total amount of SiC powder, dopant powder and chopped carbon fiber powder.
[0018] Preferably, the binder comprises polyvinyl alcohol and / or phenolic resin; the amount of the binder used is 5wt% of the total amount of SiC powder, dopant powder and chopped carbon fiber powder.
[0019] Preferably, the compression molding includes dry pressing and / or isostatic pressing.
[0020] Preferably, the initial sintering temperature is 200-300° C., and the holding time is 2-4 hours.
[0021] Preferably, the densification sintering temperature is 1900-2200° C., and the holding time is 1-2 hours.
[0022] Preferably, the particle size of the SiC powder is 0.5 to 1 μm; the particle size of the dopant powder is 0.1 to 1 μm.
[0023] The present invention provides a chopped carbon fiber reinforced silicon carbide ceramic material, comprising a SiC matrix and a dopant and chopped carbon fibers dispersed in the SiC matrix; the dopant comprises B, B 4 One or more of C and AlN; the aspect ratio of the chopped carbon fiber is greater than 10, and the length is 5 to 30 μm; the content of SiC matrix in the chopped carbon fiber reinforced silicon carbide ceramic material is ≥89wt%, the content of dopant is >0 and ≤5wt%, and the content of chopped carbon fiber is >0 and ≤6wt%; the toughness of the chopped carbon fiber reinforced silicon carbide ceramic material is 4.0MPa·m 1 / 2 above.
[0024] In the present invention, the dopant forms defects through substitution, which will destroy the symmetry of the lattice to a certain extent and produce lattice distortion, thereby enhancing the vibration activity of the lattice, improving the sintering activity of the SiC ceramic material, and ensuring that it can be sintered into porcelain; the chopped carbon fiber has a large aspect ratio and will not form a strong interface bond with the SiC ceramic due to chemical reaction. Under the action of external force, the crack can be deflected and the crack can be extended along the grain boundary, thereby improving the fracture toughness. The present invention realizes the enhancement and complementarity of materials through the composite of different components.
[0025] In addition, the silicon carbide ceramic provided by the present invention also has the advantages of low density, high compression strength, low friction coefficient and good wear resistance.
[0026] The present invention provides a method for preparing the chopped carbon fiber reinforced silicon carbide ceramic material described in the above scheme. Since the aspect ratio of the chopped carbon fiber is above 10 and the length is 5 to 30 μm, it is the same as ceramic powder in macroscopic terms and can be directly pressed into ceramic together with SiC powder, which simplifies the preparation process compared to long fibers. DETAILED DESCRIPTION
[0027] The present invention provides a chopped carbon fiber reinforced silicon carbide ceramic material, comprising a SiC matrix and a dopant and chopped carbon fibers dispersed in the SiC matrix;
[0028] The dopant includes B, B 4 One or more of C and AlN;
[0029] The chopped carbon fibers have an aspect ratio of greater than 10 and a length of 5 to 30 μm;
[0030] The content of SiC matrix in the chopped carbon fiber reinforced silicon carbide ceramic material is ≥89wt%, the content of dopant is >0 and ≤5wt%, and the content of chopped carbon fiber is >0 and ≤6wt%;
[0031] The toughness of the chopped carbon fiber reinforced silicon carbide ceramic material is 4.0 MPa·m 1 / 2 above.
[0032] In a specific embodiment, the content of SiC matrix in the chopped carbon fiber reinforced silicon carbide ceramic material can be 89wt%, 92wt%, 94wt%, 96wt%, 98wt% or 99wt%; the content of the dopant can be 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%; the content of the chopped carbon fiber can be 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or 6wt%.
[0033] In the present invention, the dopant forms defects through substitution, which to a certain extent destroys the symmetry of the lattice and produces lattice distortion, thereby enhancing the vibration activity of the lattice and improving the sintering activity of the SiC ceramic material, ensuring that it can be sintered into porcelain.
[0034] In the present invention, the aspect ratio of the chopped carbon fiber is preferably 10 to 40. In a specific embodiment, the aspect ratio of the chopped carbon fiber may be 10, 15, 20, 30 or 40; the length of the chopped carbon fiber may be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm.
[0035] In the present invention, the chopped carbon fiber has a large aspect ratio and does not form a strong interface bond with the SiC ceramic due to chemical reaction. Under the action of external force, the crack can be deflected and the crack can be extended along the grain boundary, thereby improving the fracture toughness. In the present invention, the toughness of the chopped carbon fiber reinforced silicon carbide ceramic material is 4.0MPa·m 1 / 2 More preferably, 4.0 to 4.8 MPa·m 1 / 2 .
[0036] In addition, the chopped carbon fiber also has the advantage of low density, so the density of the prepared chopped carbon fiber reinforced silicon carbide ceramic material is relatively low. In the present invention, the density of the chopped carbon fiber reinforced silicon carbide ceramic material is preferably 3.0 to 3.1 g / cm 3 In a specific embodiment, it can be 3.0 g / cm 3 、3.03g / cm 3 、3.05g / cm 3 、3.06g / cm 3 、3.07g / cm 3 or 3.08g / cm3 .
[0037] The components of the present invention cooperate to obtain the chopped carbon fiber reinforced silicon carbide ceramic material, which also has the advantages of high compressive strength and low friction coefficient. In the present invention, the compressive strength of the chopped carbon fiber reinforced silicon carbide ceramic material is preferably 2000-3000 MPa, and the friction coefficient is preferably 0.25-0.3. In a specific embodiment, the compressive strength of the chopped carbon fiber reinforced silicon carbide ceramic material can be 2000MPa, 2200MPa, 2400MPa, 2600MPa, 2800MPa or 3000MPa, and the friction coefficient can be 0.25, 0.26, 0.27, 0.28, 0.29 or 0.3.
[0038] The present invention provides a method for preparing the chopped carbon fiber reinforced silicon carbide ceramic material according to the above scheme, comprising the following steps:
[0039] The SiC powder, dopant powder, water, dispersant, binder and chopped carbon fiber powder are ball-milled and mixed, and then dried and sieved to obtain a mixed powder; the mass of the SiC powder, dopant powder and chopped carbon fiber powder is the same as the mass of the SiC matrix, dopant and chopped carbon fiber in the chopped carbon fiber reinforced silicon carbide ceramic material;
[0040] Pressing the mixed powder into a shape to obtain a green body;
[0041] The green body is subjected to primary sintering and densification sintering in sequence to obtain the chopped carbon fiber reinforced silicon carbide ceramic material.
[0042] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.
[0043] The invention ball-mills SiC powder, dopant powder, water, dispersant, binder and chopped carbon fiber powder, sieves after drying, and obtains mixed powder.
[0044] In the present invention, the particle size of the SiC powder is preferably 0.5-1 μm. In a specific embodiment, the particle size of the SiC powder may be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm. The particle size of the dopant powder is preferably 0.1-1 μm. In a specific embodiment, the particle size of the dopant powder may be 0.1 μm, 0.3 μm, 0.5 μm, 0.7 μm, 0.8 μm or 1 μm.
[0045] In the present invention, the aspect ratio of the chopped carbon fibers is greater than 10, and the length is 5 to 30 μm.
[0046] In the present invention, the dispersant preferably includes one or more of stearic acid, n-butanol, polyvinyl pyrrolidone, hexadecyl trimethyl ammonium bromide, sodium dodecyl sulfate and sodium dodecyl benzene sulfonate; the amount of the dispersant is preferably 0.1-0.5wt% of the total amount of SiC powder and chopped carbon fiber powder, and in a specific embodiment, it can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt% or 0.5wt%. In the present invention, the function of the dispersant is to disperse the materials uniformly.
[0047] In the present invention, the binder preferably includes one or more of polyvinyl alcohol (PVA), phenolic resin and polyvinyl pyrrolidone; the amount of the binder is preferably 5wt% of the total amount of SiC powder and chopped carbon fiber powder.
[0048] In the present invention, the ball milling and mixing of SiC powder, dopant powder, water, dispersant, binder and chopped carbon fiber powder preferably includes: firstly preparing SiC powder, dopant powder, water and binder into slurry, then adding dispersant to the slurry for first ball milling, and then adding chopped carbon fiber powder to the obtained ball milled slurry for second ball milling. In the present invention, the mass ratio of the total mass of the SiC powder, dopant powder and chopped carbon fiber powder to water is preferably 1:1. In the present invention, the time of the first ball milling and the second ball milling is preferably more than 2h independently. In the present invention, the ball milling media used for the first ball milling and the second ball milling are preferably SiC balls. In the present invention, the mass ratio of the total mass of the SiC powder, dopant powder and chopped carbon fiber powder to the ball milling media is preferably 1:1.5 to 3, more preferably 1:2.
[0049] The present invention has no special requirements on the rotation speeds of the first ball mill and the second ball mill, and the ball mill rotation speeds known in the art can be used. The present invention mixes the raw material powders uniformly through ball milling.
[0050] In the present invention, the drying is preferably oven drying or spray drying. In the present invention, the sieving is preferably 100 mesh sieve.
[0051] After obtaining the mixed powder, the present invention presses the mixed powder into a shape to obtain a green body.
[0052] In the present invention, the pressing molding preferably includes dry pressing and / or isostatic pressing, more preferably dry pressing first and then isostatic pressing; the pressure of the dry pressing is preferably 5-100MPa, and in a specific embodiment, the pressure of the dry pressing is preferably 5MPa, 20MPa, 40MPa, 60MPa, 80MPa or 100MPa; the pressure of the isostatic pressing is preferably 150-200MPa, and in a specific embodiment, the pressure of the isostatic pressing can be 150MPa, 160MPa, 170MPa, 180MPa, 190MPa or 200MPa. The present invention has no special requirements for the time of the pressing molding. The present invention first dry presses and then isostatic presses, which is conducive to obtaining a green body with more uniform density, more stable high-temperature sintering shrinkage, and smaller fluctuations.
[0053] After obtaining the green body, the present invention sequentially performs primary sintering and densification sintering on the green body to obtain the chopped carbon fiber reinforced silicon carbide ceramic material.
[0054] In the present invention, the temperature of the initial sintering is preferably 600-1200°C, and the holding time is preferably 2-4h; in a specific embodiment, the temperature of the initial sintering can be 600°C, 800°C, 1000°C or 1200°C, and the holding time of the initial sintering can be 2h, 3h or 4h. In the present invention, the rate of heating to the temperature of the initial sintering is preferably no more than 10°C / min. The present invention uses the initial sintering to give the green body a certain strength to prevent cracking due to direct high-temperature sintering.
[0055] In the present invention, the temperature of the densification sintering is preferably 1900-2200°C, and the holding time is preferably 1-2 hours; in a specific embodiment, the temperature of the densification sintering can be 1900°C, 2000°C, 2100°C or 2200°C, and the densification sintering time can be 1 hour, 1.5 hours or 2 hours. In the present invention, the rate of heating from the initial sintering temperature to the densification sintering temperature is preferably no more than 10°C / min.
[0056] In the present invention, the densification sintering is preferably carried out in an inert atmosphere, and the inert atmosphere is preferably an argon atmosphere. In the densification sintering process, the binder is discharged and the ceramic is densified at the same time.
[0057] The present invention adopts chopped carbon fibers to prepare chopped carbon fiber reinforced silicon carbide ceramic materials, which simplifies the process flow compared with adopting long fibers.
[0058] The chopped carbon fiber reinforced silicon carbide ceramic material and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0059] Example 1
[0060] SiC powder (particle size 0.5-0.8 μm, 98.5 wt%), dopant B 4 C powder (particle size W0.5, 0.5wt%), 30μm short-cut C fiber (aspect ratio 30, 1wt%), 100g in total, 5g PVA as binder, SiC powder, dopant B 4 C powder, binder and 100g water are prepared into slurry, 0.1g of polyvinyl pyrrolidone is added, 200g of SiC balls are used as ball milling media, mixed for 24h, and then short-cut C fibers are added and mixed for 12h. The powder obtained after spray drying is molded on a flat vulcanizer at 16MPa pressure, and then isostatically pressed at a pressure of 200MPa to obtain a green body. The green body is heated to 220℃ at a rate of 2℃ / min and kept warm for 2h for initial sintering, and then heated to 2100℃ at a rate of 3.5℃ / min for dense sintering in an Ar gas atmosphere at normal pressure. The holding time is 1h, and the density of the obtained short-cut carbon fiber reinforced silicon carbide ceramic material is 3.08g / cm 3 , compression strength is 3000MPa, toughness reaches 4.8MPa·m 1 / 2 , the friction coefficient is 0.26. Among them, the compression strength is tested according to the JB / T 6374-2020 standard, and the toughness is measured by a Vickers hardness tester.
[0061] Example 2
[0062] SiC powder (particle size 0.5-0.8 μm, 96.5 wt%), dopant B 4 C powder (particle size W1.5, 0.5wt%), 10μm short-cut C fiber (aspect ratio 30, 3wt%), 5g phenolic resin as binder, SiC powder, dopant B 4 C powder, binder and 100g water are prepared into slurry, 0.1g of polyvinyl pyrrolidone is added, 200g SiC balls are used as ball milling media, mixed for 24h, and then short-cut C fibers are added and mixed for 12h. The powder obtained after drying is molded on a flat vulcanizer at 16MPa pressure, and then isostatically pressed at 200MPa pressure to obtain a green body. The green body is heated to 220℃ at a rate of 2℃ / min and kept warm for 2h for initial sintering, and then heated to 2200℃ at a rate of 3.5℃ / min for dense sintering in an Ar gas atmosphere at normal pressure. The holding time is 1h, and the density of the obtained short-cut carbon fiber reinforced silicon carbide ceramic material is 3.06g / cm 3 , compression strength is 2800MPa, toughness reaches 4.5MPa·m 1 / 2 , the friction coefficient is 0.27.
[0063] Example 3
[0064] SiC powder (particle size of 0.5-0.8 μm, 89 wt%), AlN powder (particle size of 1 μm, 5 wt%) as dopant, 5 μm short-cut C fiber (aspect ratio of 1.6 wt%) as second phase, 100 g in total, 5 g phenolic resin as binder, SiC powder, AlN powder, binder and 100 g water are prepared into slurry, 0.1 g polyvinyl pyrrolidone is added, 200 g SiC ball is used as ball milling medium, mixed for 24 h, then short-cut C fiber is added and mixed for 12 h. The powder obtained after drying is molded on a flat vulcanizer at 16 MPa pressure, and then isostatically pressed at 200 MPa pressure to obtain a green body. The green body was heated to 220°C at a rate of 2°C / min and kept at that temperature for 2h for primary sintering, and then heated to 2000°C at a rate of 3.5°C / min for dense sintering in an Ar gas atmosphere at normal pressure for 2h. The density of the obtained short carbon fiber reinforced silicon carbide ceramic material was 3.03g / cm 3 , compression strength is 2600MPa, toughness is 4.3MPa·m 1 / 2 , the friction coefficient is 0.28.
[0065] Example 4
[0066] SiC powder (particle size of 0.5-0.8 μm, 89 wt%), B powder (particle size of W0.5, 5 wt%) as dopant, 5 μm short-cut C fiber (aspect ratio of 10, 6 wt%) as second phase, 100 g in total, 5 g phenolic resin as binder, SiC powder, B powder, binder and 100 g water are prepared into slurry, 0.1 g polyvinyl pyrrolidone is added, 200 g SiC ball is used as ball milling medium, mixed for 24 h, and short-cut C fiber is added and mixed for 12 h. The powder obtained after drying is molded on a flat vulcanizer at 16 MPa pressure, and then isostatically pressed at 200 MPa pressure to obtain a green body. The green body was heated to 220°C at a rate of 2°C / min and kept at that temperature for 2h for primary sintering, and then heated to 2000°C at a rate of 3.5°C / min for dense sintering in an Ar gas atmosphere at normal pressure for 2h to obtain a chopped carbon fiber reinforced silicon carbide ceramic material with a density of 3.0g / cm 3 , compression strength reaches 2400MPa, toughness reaches 4.0MPa·m 1 / 2 , the friction coefficient is 0.29.
[0067] Comparative Example 1
[0068] No dopant was added, SiC powder (particle size of 0.5-0.8 μm) and 5 μm short-cut C fiber (aspect ratio of 10, 6 wt%) were used as the second phase, totaling 100 g, phenolic resin was used as a binder of 5 g, SiC powder, binder and 100 g water were prepared into a slurry, 0.1 g of polyvinyl pyrrolidone was added, 200 g of SiC balls were used as ball milling media, mixed for 24 h, and then short-cut C fiber was added and mixed for 12 h. The powder obtained after drying was molded on a flat vulcanizer at 16 MPa pressure, and then isostatically pressed at 200 MPa pressure to obtain a green body. The green body was heated to 220 ° C at a rate of 2 ° C / min and kept warm for 2 h for initial sintering, and then heated to 2000 ° C at a rate of 3.5 ° C / min for dense sintering in an Ar gas atmosphere at normal pressure, and the holding time was 2 h, and the density of the short-cut carbon fiber reinforced silicon carbide ceramic material was 2.8 g / cm 3 , compression strength reaches 100MPa, toughness reaches 2MPa·m 1 / 2 , the friction coefficient reaches 0.8. This ratio does not result in porcelain sintering and has poor strength performance.
[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A chopped carbon fiber reinforced silicon carbide ceramic material, characterized in that: The invention comprises a SiC matrix and a dopant and chopped carbon fibers dispersed in the SiC matrix; The dopant includes one or more of B, B4C and AlN; The chopped carbon fibers have an aspect ratio of greater than 10 and a length of 5 to 30 μm; The content of SiC matrix in the chopped carbon fiber reinforced silicon carbide ceramic material is ≥89wt%, the content of dopant is >0 and ≤5wt%, and the content of chopped carbon fiber is >0 and ≤6wt%; The toughness of the chopped carbon fiber reinforced silicon carbide ceramic material is 4.0 MPa·m 1 / 2 above.
2. The chopped carbon fiber reinforced silicon carbide ceramic material according to claim 1, characterized in that: The compressive strength of the chopped carbon fiber reinforced silicon carbide ceramic material is 2000-3000 MPa.
3. The chopped carbon fiber reinforced silicon carbide ceramic material according to claim 1 or 2, characterized in that: The density of the chopped carbon fiber reinforced silicon carbide ceramic material is 3.0-3.1 g / cm 3 , the friction coefficient is 0.25~0.
3.
4. The method for preparing the chopped carbon fiber reinforced silicon carbide ceramic material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The SiC powder, dopant powder, water, dispersant, binder and chopped carbon fiber powder are ball-milled and mixed, and then dried and sieved to obtain a mixed powder; the mass of the SiC powder, dopant powder and chopped carbon fiber powder is the same as the mass of the SiC matrix, dopant and chopped carbon fiber in the chopped carbon fiber reinforced silicon carbide ceramic material; Pressing the mixed powder into a shape to obtain a green body; The green body is subjected to primary sintering and densification sintering in sequence to obtain the chopped carbon fiber reinforced silicon carbide ceramic material.
5. The preparation method according to claim 4, characterized in that: The dispersant includes one or more of stearic acid, n-butanol, polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate; the amount of the dispersant is 0.1-0.5wt% of the total amount of SiC powder, dopant powder and chopped carbon fiber powder.
6. The preparation method according to claim 4, characterized in that: The binder includes polyvinyl alcohol and / or phenolic resin; the amount of the binder is 5wt% of the total amount of SiC powder, dopant powder and chopped carbon fiber powder.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The compression molding includes dry pressing and / or isostatic pressing.
8. The preparation method according to claim 4, characterized in that: The initial sintering temperature is 200-300° C., and the heat preservation time is 2-4 hours.
9. The preparation method according to claim 4, characterized in that: The densification sintering temperature is 1900-2200° C., and the heat preservation time is 1-2 hours.
10. The preparation method according to claim 3, characterized in that: The particle size of the SiC powder is 0.5-1 μm; the particle size of the dopant powder is 0.1-1 μm.
Citation Information
Cited By
Carbon fiber reinforced silicon carbide ceramic-based composite material and preparation method thereof
CN121181353A